Acod1-mediated inhibition of aerobic glycolysis suppresses osteoclast differentiation and attenuates bone erosion in arthritis - Kachler, Katerina; Andreev, Darja; Thapa, Shreeya; Royzman, Dmytro; Gießl, Andreas; Karuppusamy, Shobika; Llerins Perez, Mireia; Liu, Mengdan; Hofmann, Jörg; Geßner, Arne; Meng, Xianyi; Rauber, Simon; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: Metabolic changes are crucially involved in osteoclast development and may contribute to bone degradation in rheumatoid arthritis (RA). The enzyme aconitate decarboxylase 1 (Acod1) is known to link the cellular function of monocyte-derived macrophages to their metabolic status. As osteoclasts derive from the monocyte lineage, we hypothesised a role for Acod1 and its metabolite itaconate in osteoclast differentiation and arthritis-associated bone loss. Methods: Itaconate levels were measured in human peripheral blood mononuclear cells (PBMCs) of patients with RA and healthy controls by mass spectrometry. Human and murine osteoclasts were treated with the itaconate derivative 4-octyl-itaconate (4-OI) in vitro. We examined the impact of Acod1-deficiency and 4-OI treatment on bone erosion in mice using K/BxN serum-induced arthritis and human TNF transgenic (hTNFtg) mice. SCENITH and extracellular flux analyses were used to evaluate the metabolic activity of osteoclasts and osteoclast progenitors. Acod1-dependent and itaconate-dependent changes in the osteoclast transcriptome were identified by RNA sequencing. CRISPR/Cas9 gene editing was used to investigate the role of hypoxia-inducible factor (Hif)-1α in Acod1-mediated regulation of osteoclast development. Results: Itaconate levels in PBMCs from patients with RA were inversely correlated with disease activity. Acod1-deficient mice exhibited increased osteoclast numbers and bone erosion in experimental arthritis while 4-OI treatment alleviated inflammatory bone loss in vivo and inhibited human and murine osteoclast differentiation in vitro. Mechanistically, Acod1 suppressed osteoclast differentiation by inhibiting succinate dehydrogenase-dependent production of reactive oxygen species and Hif1α-mediated induction of aerobic glycolysis. Conclusion: Acod1 and itaconate are crucial regulators of osteoclast differentiation and bone loss in inflammatory arthritis.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Bone Density; Inflammation; Osteoporosis

A MINIMAL-INVASIVE METHOD TO RETRIEVE AND IDENTIFY ENTHESEAL TISSUE FROM PSORIATIC ARTHRITIS PATIENTS - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Soare, A.; Bräuer, Lars; Rech, Jürgen; Simon, David; Kleyer, Arnd; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

A novel Slide-seq based image processing software to identify gene expression at the single cell level - Götz, Theresa; Cong, X.; Rauber, Simon; Angeli, Mario Raphael; Lang, E. W.; Ramming, Alina; Schmidkonz, Christian (Journal of Pathology Informatics, 2024)
Analysis of gene expression at the single-cell level could help predict the effectiveness of therapies in the field of chronic inflammatory diseases such as arthritis. Here, we demonstrate an adopted approach for processing images from the Slide-seq method. Using a puck, which consists of about 50,000 DNA barcode beads, an RNA sequence of a cell is to be read. The pucks are repeatedly brought into contact with liquids and then recorded with a conventional epifluorescence microscope. The image analysis initially consists of stitching the partial images of a sequence recording, registering images from different sequences, and finally reading out the bases. The new method enables the use of an inexpensive epifluorescence microscope instead of a confocal microscope.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Cell segmentation; Deep neural networks; DNN complexity; Pruning; Slide-seq

Butyrophilin 2a2 (Btn2a2) expression on thymic epithelial cells promotes central T cell tolerance and prevents autoimmune disease: Btn2a2 promotes central tolerance - Frech, Michael; Danzer, Heike; Uchil, Pooja; Azizov, Vugar; Schmid, Eva; Schälter, Fabian; Dürholz, Kerstin; Mauro, Daniele; Rauber, Simon; Munoz Becerra, Luis; Taher, Leila; Ciccia, Francesco; et al. (Journal of Autoimmunity, 2023)
Butyrophilins are surface receptors belonging to the immunoglobulin superfamily. While several members of the butyrophilin family have been implicated in the development of unconventional T cells, butyrophilin 2a2 (Btn2a2) has been shown to inhibit conventional T cell activation. Here, we demonstrate that in steady state, the primary source of Btn2a2 are thymic epithelial cells (TEC). Absence of Btn2a2 alters thymic T cell maturation and bypasses central tolerance mechanisms. Furthermore, Btn2a2−/− mice develop spontaneous autoimmunity resembling human primary Sjögren's Syndrome (pSS), including formation of tertiary lymphoid structures (TLS) in target organs. Ligation of Btn2a2 on developing thymocytes is associated with reduced TCR signaling and CD5 levels, while absence of Btn2a2 results in increased TCR signaling and CD5 levels. These results define a novel role for Btn2a2 in promoting central tolerance by modulating TCR signaling strength and indicate a potential mechanism of pSS development.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Autoimmune disease; Autoimmunity; Butyrophilin 2a2 (Btn2a2); Central tolerance; Primary sjögren's syndrome (pSS); Thymic epithelial cells (TEC)

CD19-CAR T-cell therapy induces deep tissue depletion of B cells - Tur, Carlo; Eckstein, Markus; Velden, Joachim; Rauber, Simon; Bergmann, Christina; Auth, Janina; Bucci, Laura; Corte, Giulia; Hagen, Melanie; Wirsching, Andreas; Grieshaber Bouyer, Ricardo; Reis, Petra; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives CD19-targeting chimeric antigen receptor (CAR) T-cell therapy can induce long-term drug-free remission in patients with autoimmune diseases (AIDs). The efficacy of CD19-CAR T-cell therapy is presumably based on deep tissue depletion of B cells; however, such effect has not been proven in humans in vivo. Methods Sequential ultrasound-guided inguinal lymph node biopsies were performed at baseline and after CD19-CAR T-cell therapy in patients with AIDs. Results were compared with lymph node biopsies from rituximab (RTX)-treated AID patients with absence of peripheral B cells. Conventional and immunohistochemistry staining were performed on lymph node tissue to assess architecture as well the number of B cells, follicular dendritic cells (FDCs), plasma cells, T cells and macrophages. Results Sequential lymph node biopsies were analysed from five patients with AID before and after CD19-CAR T-cell therapy and from five patients with AID after RTX treatment. In addition, non-lymphoid organ biopsies (colon, kidney and gallbladder) from three additional patients with AID after CD19-CAR T-cell therapy were analysed. CD19+ and CD20+ B cells were completely depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX treatment. Plasma cells, T cells and macrophages in the lymph nodes remained unchanged. Follicular structures were disrupted and FDCs were depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX. Non-lymphoid organs were completely depleted of B cells. Discussion This study demonstrates complete B-cell depletion in secondary lymphoid tissues of patients with AIDs following CD19-CAR T-cell therapy combined with standard lymphodepleting therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Autoimmune Diseases; B-Lymphocytes; Rituximab; Ultrasonography

CD200+ fibroblasts form a pro-resolving mesenchymal network in arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Soare, Alina; Treutlein, Christoph; Kemble, Samuel; Mahony, Christopher B.; Geisthoff, Manuel; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Xu, Cong; et al. (Nature Immunology, 2024)
Fibroblasts are important regulators of inflammation, but whether fibroblasts change phenotype during resolution of inflammation is not clear. Here we use positron emission tomography to detect fibroblast activation protein (FAP) as a means to visualize fibroblast activation in vivo during inflammation in humans. While tracer accumulation is high in active arthritis, it decreases after tumor necrosis factor and interleukin-17A inhibition. Biopsy-based single-cell RNA-sequencing analyses in experimental arthritis show that FAP signal reduction reflects a phenotypic switch from pro-inflammatory MMP3+/IL6+ fibroblasts (high FAP internalization) to pro-resolving CD200+DKK3+ fibroblasts (low FAP internalization). Spatial transcriptomics of human joints indicates that pro-resolving niches of CD200+DKK3+ fibroblasts cluster with type 2 innate lymphoid cells, whereas MMP3+/IL6+ fibroblasts colocalize with inflammatory immune cells. CD200+DKK3+ fibroblasts stabilized the type 2 innate lymphoid cell phenotype and induced resolution of arthritis via CD200–CD200R1 signaling. Taken together, these data suggest a dynamic molecular regulation of the mesenchymal compartment during resolution of inflammation.
Created from Fastlane, Scopus look-up

Concise report: a minimal-invasive method to retrieve and identify entheseal tissue from psoriatic arthritis patients - Pachowsky, Milena; Raimondo, Maria Gabriella; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (Annals of the Rheumatic Diseases, 2022)
Objectives To establish a minimally invasive biopsy technique for the analysis of entheseal tissue in patients with psoriatic arthritis (PsA). Methods Human cadavers were used for establishing the technique to retrieve tissue from the lateral humeral epicondyle enthesis (cadaveric biopsies). After biopsy, the entire enthesis was surgically resected (cadaveric resections). Biopsies and resections were assessed by label-free second harmonic generation (SHG) microscopy. The same technique was then applied in patients with PsA with definition of entheseal tissue by SHG, staining of CD45+immune cells and RNA extraction. Results Entheseal biopsies from five cadavers allowed the retrieval of entheseal tissue as validated by the analysis of resection material. Microscopy of biopsy and resection sections allowed differentiation of entheseal, tendon and muscle tissue by SHG and definition of specific intensity thresholds for entheseal tissue. In subsequent entheseal biopsies of 10 PsA patients: the fraction of entheseal tissue was high (65%) and comparable to cadaveric biopsies (68%) as assessed by SHG microscopy. Furthermore, PsA biopsies showed immune cell infiltration and sufficient retrieval of RNA for further molecular analysis. Conclusion Entheseal biopsy of the lateral epicondyle is feasible in patients with PsA allowing reliable retrieval of entheseal tissue and its identification by SHG microscopy.
CRIS-Team WoS Importer:2022-05-13

Cutting Edge: Homeostasis of Innate Lymphoid Cells Is Imbalanced in Psoriatic Arthritis - Soare, Alina; Weber, Stefanie; Maul, Lisa; Rauber, Simon; Gheorghiu, Ana Maria; Luber, Markus; Houssni, Ismail; Kleyer, Arnd; von Pickardt, Gero; Gado, Manuel; Simon, David; Rech, Jürgen; et al. (Journal of Immunology, 2018)
Innate lymphoid cells (ILC) have a high potency for cytokine production independent of specific Ag stimulation. Imbalance of ILC subsets may influence cytokine production in humans and hence be associated with the development of inflammatory disease. Evidence for an imbalance of ILC homeostasis in human disease, however, is very limited to date. In this study we show that psoriatic arthritis (PsA), a severe disease of the joints depending on the activation of the IL-23/IL-17 pathway, is characterized by a skewed ILC homeostasis. Circulating ILC3s as potent source of IL-17/IL-22 were elevated in active PsA, whereas ILC2s, which produce proresolving cytokines, were decreased. The ILC2/ILC3 ratio was significantly correlated with clinical disease activity scores and the presence of imaging signs of joint inflammation and bone damage. Multivariable analysis showed that a high ILC2/ILC3 ratio is associated with remission in PsA, suggesting that specific alterations of ILC homeostasis control disease activity in PsA.
EVALuna2:13524

Dipeptidylpeptidase 4 as a Marker of Activated Fibroblasts and a Potential Target for the Treatment of Fibrosis in Systemic Sclerosis - Soare, Alina; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Dees, Clara; Rauber, Simon; Wohlfahrt, Thomas; Chen, Chih Wei; Ludolph, Ingo; Horch, Raymund E.; Bäuerle, Tobias; von Hörsten, Stephan; Mihai, Carina; et al. (Arthritis and Rheumatology, 2020)
Objective: Expression of dipeptidylpeptidase 4 (DPP-4) identifies a dermal fibroblast lineage involved in scarring during wound healing. The role of DDP-4 in tissue fibrosis is, however, unknown. The aim of the present study was to evaluate DPP-4 as a potential target for the treatment of fibrosis in patients with systemic sclerosis (SSc). Methods: Expression of DPP-4 in skin biopsy samples and dermal fibroblasts was analyzed by real-time polymerase chain reaction, immunofluorescence, and Western blot analyses. The activity of DPP-4 was modulated by overexpression, knockdown, and pharmacologic inhibition of DPP4 using sitagliptin and vildagliptin. The effects of DPP4 inhibition were analyzed in human dermal fibroblasts and in different mouse models of SSc (each n = 6). Results: The expression of DPP-4 and the number of DPP-4–positive fibroblasts were increased in the fibrotic skin of SSc patients, in a transforming growth factor β (TGFβ)–dependent manner. DPP-4–positive fibroblasts expressed higher levels of myofibroblast markers and collagen (each P < 0.001 versus healthy controls). Overexpression of DPP4 promoted fibroblast activation, whereas pharmacologic inhibition or genetic inactivation of DPP4 reduced the proliferation, migration, and expression of contractile proteins and release of collagen (each P < 0.001 versus control mice) by interfering with TGFβ-induced ERK signaling. DPP4-knockout mice were less sensitive to bleomycin-induced dermal and pulmonary fibrosis (P < 0.0001 versus wild-type controls). Treatment with DPP4 inhibitors promoted regression of fibrosis in mice that had received bleomycin challenge and mice with chronic graft-versus-host disease, and ameliorated fibrosis in TSK1 mice (each P < 0.001 versus untreated controls). These antifibrotic effects were associated with a reduction in inflammation. Conclusion: DPP-4 characterizes a population of activated fibroblasts and shows that DPP-4 regulates TGFβ-induced fibroblast activation in the fibrotic skin of SSc patients. Inhibition of DPP4 exerts potent antifibrotic effects when administered in well-tolerated doses. As DPP4 inhibitors are already in clinical use for diabetes, these results may have direct translational implications for the treatment of fibrosis in patients with SSc.
CRIS-Team Scopus Importer:2020-01-10

Dipeptidyl-Peptidase-4 (DPP4) Positive Fibroblast Subpopulation Promotes Fibrosis and Are a Molecular Target for Treatment of Fibrosis - Soare, Alina; Rauber, Simon; Wohlfahrt, Thomas; Dees, Clara; Liang, Ruifang; Zhang, Yun; Chen, Chih-Wei; Distler, Oliver; Mihai, Carina; Schett, Georg; Distler, Jörg; Ramming, Andreas (2016)
EVALuna2:35065

Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Agarwal, Rahul; Götz, Theresa Ida; Soare, Alina; Cordes, Michael; Prante, Olaf; Prante, Olaf; Bergmann, Christina; Kleyer, Arnd; Ritt, Philipp; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG 4 -related disease. Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG 4 -related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68 Ga-FAP inhibitor (FAPI)-04), 18 F-fluorodeoxyglucose (FDG), MRI and histopathological assessment. In a longitudinal approach, 18 F-FDG and 68 Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Results Using combination of 68 Ga-FAPI-04 and 18 F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG 4 -related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18 F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG 4 + cells in histology, while 68 Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Conclusion FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG 4 -related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG 4 -related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team Scopus Importer:2020-10-30
Keywords: fibroblasts; health care; inflammation; outcome assessment

Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Götz, Theresa Ida; Soare, A.; Cordes, Michael; Prante, Olaf; Ritt, Philipp; Bäuerle, Tobias; Köhner, Markus; Haberkorn, U.; Kuwert, Torsten; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2021)
Ziel/Aim To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG4-related disease. Methodik/Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG4-related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68Ga-FAP inhibitor (FAPI)-04), 18F-fluorodeoxyglucose (FDG), magnetic resonance imaging (MRI) and histopathological assessment. In a longitudinal approach, 18F-FDG and 68Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Ergebnisse/Results Using combination of 68Ga-FAPI-04 and 18F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG4-related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG4 + cells in histology, while 68Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Schlussfolgerungen/Conclusions FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG4-related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG4-related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team WoS Importer:2022-01-07

Effects of different B-cell-depleting strategies on the lymphatic tissue - Tur, Carlo; Eckstein, Markus; Bucci, Laura; Auth, Janina; Bergmann, Christina; Rauber, Simon; Hagen, Melanie; Nöthling, Danae-Mona; Böltz, Sebastian; Wirsching, Andreas; Tascilar, Koray; Fagni, Filippo; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: To assess the efficacy of new protein-based B cell depletion with glyco-engineered anti-CD20 antibody obinutuzumab (OBI) and the CD19/CD3 T cell engager blinatumomab (BLI) in patients with autoimmune diseases (AIDs) in comparison to rituximab (RTX) and CD19 chimeric antigen receptor (CAR) T cell therapy. Methods: Sequential inguinal lymph node biopsies were taken before and after treatment with OBI-, BLI-, RTX- and CD19-CAR T cells in patients with AID. CD19+ and CD20+ B cells, plasma cells, T cells and macrophages were analysed by immunohistochemistry. Changes in follicular architecture (follicular dendritic cells, T follicular helper cells, proliferation) were also assessed. Results: Baseline and follow-up lymph node biopsies from 24 patients with AID (OBI, 4; BLI, 4; RTX, 4; CD19-CAR T cells, 12) were analysed. B cell depletion was confirmed in all CD19-CAR T cell-treated patients but only in 1 (OBI) out of 12 protein-based B cell-treated patients. Likewise, follicular architecture was disrupted in all CD19-CAR T cell-treated patients but only in 1 (OBI) out of 12 protein-based B cell-treated patients. B cell depletion efficacy in the lymph nodes was 100% for CD19-CAR T cells, 92% for OBI, 86% for RTX and 69% for BLI. Plasma cells were reduced but not depleted in all treatment approaches. CD3+ T cells and CD68+ macrophages remained unaffected. Peripheral blood B cell depletion occurred in all but 1 BLI-treated patient. B cell depletion was associated with stable drug-free remission, whereas a reduction in B cell numbers without depletion required retreatment with immunomodulatory drugs. Conclusions: Protein-based B cell depletion reduces but usually does not deplete B cells in lymph nodes leaving the follicular architecture intact and being associated with disease recurrence.
CRIS-Team Scopus Importer:2025-07-18

Entheseal Biopsy Approach: An Ultrasound-guided Method for Retrieval of Entheseal Tissue from Psoriatic Arthritis Patients - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Entheseal tissue signature in response to IL-17A inhibition in psoriatic arthritis: results from the EBIO entheseal biopsy study - Raimondo, Maria Gabriella; Mohammadian, Hashem; Rauber, Simon; Alivernini, Stefano; Fedorchenko, Vladyslav; Rigau, Aleix Rius; Angeli, Mario Raphael; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Labinsky, Hannah; Ramming, Alina; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: Enthesitis, a hallmark of psoriatic arthritis (PsA), reflects the interplay between mechanical stress and immune dysregulation at tendon-bone interfaces. This study investigates the cellular and molecular responses in entheseal tissues following interleukin (IL)-17A inhibition in patients with active PsA. Methods: In this prospective, interventional phase 4 trial, we enrolled 10 patients with enthesitis of the lateral epicondyle, performed entheseal biopsies, and analysed tissues by imaging mass cytometry (IMC) and spatial transcriptomics before and after treatment. Results: Following 24 weeks of IL-17A inhibition, 9/10 patients of the cohort clinically responded to treatment as assessed by Disease Activity in Psoriatic Arthritis (DAPSA), Spondyloarthritis research consortium of canada (SPARCC) score, and power Doppler sonography. IMC analysis showed significant reductions of enthesitis-related immune cell populations, in particular IL-17-producing CD4, CD8, CD4neg/CD8negT cells, granulocytes, and innate lymphoid cells type 3. Spatial transcriptomics revealed that CD200+DKK3+ fibroblasts and innate lymphoid cells type 2 expanded and formed an anti-inflammatory niche upon treatment. Notably, IL-17A inhibition led to decreased osteoblast differentiation markers, suggesting a potential mechanism to inhibit pathological bone formation. Conclusions: These findings underline the pivotal role of IL-17A in enthesitis, showing that IL-17A inhibition profoundly modulates the tissue microenvironment of entheses in PsA.
CRIS-Team Scopus Importer:2025-11-07

Fibroblast Activation Protein (FAP) PET-CT for Depicting Inflammatory Joint Damage in Patients with Psoriatic Arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Raimondo, Maria Gabriella; Labinsky, Hannah; Treutlein, Christoph; Knitza, Johannes; Maschauer, Simone; Roemer, Frank; Prante, Olaf; Kuwert, Torsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

FIBROBLAST ACTIVATION PROTEIN (FAP) PET-CT IMAGING ALLOWS TO DEPICT INFLAMMATORY JOINT REMODELING IN PATIENTS WITH PSORIATIC ARTHRITIS - Schmidkonz, Christian; Rauber, Simon; Raimondo, Maria Gabriella; Labinsky, Hannah; Atzinger, Armin; Treutlein, Christoph; Knitza, Johannes; Maschauer, Simone; Roemer, Frank; Prante, Olaf; Kuwert, Torsten; Canete, J. D. D.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

IL-9-Producing Innate Lymphoid Cells - Keyplayers That Orchestrate Resolution of Chronic Inflammation in Arthritis - Rauber, Simon; Luber, Markus; Weber, Stefanie; Maul, Lisa; Soare, Alina; Wohlfahrt, Thomas; Bozec, Aline; Herrmann, Martin; Zaiss, Mario; Fearon, Ursula; Veale, Douglas J.; Canete, Juan; et al. (2017)
EVALuna2:33440

INNATE LYMPHOID CELLS CORRELATE WITH DISEASE ACTIVITY AND BONE REMODELLING IN PSORIATIC ARTHRITIS - Soare, A.; Weber, Stefanie; Maul, L.; Rauber, Simon; Gheorghiu, A. M.; Houssni, I.; Kleyer, Arnd; Luber, M.; Rech, Jürgen; Schett, Georg; Distler, Jörg; Ramming, A. (2018)
EVALuna2:34985

Innate Lymphoid Cells - New Players in Psoriatic Arthritis - Soare, Alina; Weber, Stefanie; Maul, Lisa; Gheorghiu, Ana Maria; Housni, Ismail; Kleyer, Arnd; Luber, Markus; Rauber, Simon; Simon, David; Rech, Jürgen; Schett, Georg; Distler, Jörg; et al. (2017)
EVALuna2:33444

JAK Inhibition Re-balances Gene Expression Profile of Circulating Immune Cells in Patients with Psoriatic Arthritis - Raimondo, Maria Gabriella; Anchang, Charles Gwellem; Labinsky, Hannah; Saad, Mina saad aziz; Rauber, Simon; Vogg, Mario; Kampylafka, Eleni; Knitza, Johannes; Soare, Alina; Schett, Georg; Ramming, Andreas (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Keratinocyte-derived S100A9 modulates neutrophil infiltration and affects psoriasis-like skin and joint disease - Mellor, Liliana F.; Gago-Lopez, Nuria; Bakiri, Latifa; Schmidt, Felix N.; Busse, Bjorn; Rauber, Simon; Jimenez, Maria; Megias, Diego; Oterino-Soto, Sergio; Sanchez-Prieto, Ricardo; Grivennikov, Sergei; Pu, Xinzhu; et al. (Annals of the Rheumatic Diseases, 2022)
Objectives S100A9, an alarmin that can form calprotectin (CP) heterodimers with S100A8, is mainly produced by keratinocytes and innate immune cells. The contribution of keratinocyte-derived S100A9 to psoriasis (Ps) and psoriatic arthritis (PsA) was evaluated using mouse models, and the potential usefulness of S100A9 as a Ps/PsA biomarker was assessed in patient samples. Methods Conditional S100A9 mice were crossed with DKO* mice, an established psoriasis-like mouse model based on inducible epidermal deletion of c-Jun and JunB to achieve additional epidermal deletion of S100A9 (TKO* mice). Psoriatic skin and joint disease were evaluated in DKO* and TKO* by histology, microCT, RNA and proteomic analyses. Furthermore, S100A9 expression was analysed in skin, serum and synovial fluid samples of patients with Ps and PsA. Results Compared with DKO* littermates, TKO* mice displayed enhanced skin disease severity, PsA incidence and neutrophil infiltration. Altered epidermal expression of selective pro-inflammatory genes and pathways, increased epidermal phosphorylation of STAT3 and higher circulating TNF alpha were observed in TKO* mice. In humans, synovial S100A9 levels were higher than the respective serum levels. Importantly, patients with PsA had significantly higher serum concentrations of S100A9, CP, VEGF, IL-6 and TNF alpha compared with patients with only Ps, but only S100A9 and CP could efficiently discriminate healthy individuals, patients with Ps and patients with PsA. Conclusions Keratinocyte-derived S100A9 plays a regulatory role in psoriatic skin and joint disease. In humans, S100A9/CP is a promising marker that could help in identifying patients with Ps at risk of developing PsA.
CRIS-Team WoS Importer:2022-07-15

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate

Mast cells in early rheumatoid arthritis associate with disease severity and support B cell autoantibody production - Rivellese, Felice; Mauro, Daniele; Nerviani, Alessandra; Pagani, Sara; Fossati-Jimack, Liliane; Messemaker, Tobias; Kurreeman, Fina A.S.; Toes, René E.M.; Rauber, Simon; Schett, Georg; Jones, Gareth W.; Jones, Simon A.; et al. (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: Mast cells (MCs) are involved in the pathogenesis of rheumatoid arthritis (RA). However, their contribution remains controversial. To establish their role in RA, we analysed their presence in the synovium of treatment-naïve patients with early RA and their association and functional relationship with histological features of synovitis. METHODS: Synovial tissue was obtained by ultrasound-guided biopsy from treatment-naïve patients with early RA (n=99). Immune cells (CD3/CD20/CD138/CD68) and their relationship with CD117+MCs in synovial tissue were analysed by immunohistochemistry (IHC) and immunofluorescence (IF). The functional involvement of MCs in ectopic lymphoid structures (ELS) was investigated in vitro, by coculturing MCs with naïve B cells and anticitrullinated protein antibodies (ACPA)-producing B cell clones, and in vivo in interleukin-27 receptor alpha (IL27ra)-deficient and control mice during antigen-induced arthritis (AIA). RESULTS: High synovial MC counts are associated with local and systemic inflammation, autoantibody positivity and high disease activity. IHC/IF showed that MCs reside at the outer border of lymphoid aggregates. Furthermore, human MCs promote the activation and differentiation of naïve B cells and induce the production of ACPA, mainly via contact-dependent interactions. In AIA, synovial MC numbers increase in IL27ra deficient mice, in association with ELS and worse disease activity. CONCLUSIONS: Synovial MCs identify early RA patients with a severe clinical form of synovitis characterised by the presence of ELS.
EVALuna2:34669

Matrix stiffness regulates profibrotic fibroblast differentiation and fibrotic niche activation in systemic sclerosis - Ueberall, Ludwig; Mohammadian, Hashem; Demmler, Richard; Ariza, Yuko; Tripal, Philipp; Anchang, Charles Gwellem; Weber, Stefanie; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Chang, Jiyang; Huang, Kaiyue; Distler, Jörg H.W.; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: Fibrosis progression in systemic sclerosis (SSc) has been attributed to matrix stiffness. Despite extensive research on fibroblast heterogeneity and subset imbalances in fibrotic disorders, the interplay between biomechanical cues and fibroblast dynamics remains largely unexplored. Here, we investigate how matrix stiffness alters fibroblast transcriptional state and influences lineage specification in fibrotic skin. Methods: We employed a collagen I-based 3-dimensional culture system to expose fibroblasts to varying levels of matrix stiffness, followed by RNA sequencing to identify stiffness-responsive gene expression signature. We integrated single-cell RNA sequencing data from SSc and healthy skin samples to identify fibroblast subsets associated with this signature. Spatial transcriptomic analyses were performed to localise these fibroblasts and their associations with the fibrotic niche. Results: Fibroblasts subjected to increased matrix stiffness exhibited a distinct transcriptional signature, amplified in SSc patients and enriched in PI16+ progenitor-like cells within the SFRP2+ fibrotic compartment. Further analysis indicated that PI16+ fibroblasts are predisposed to SFRP2+ COMP+ PU.1+ myofibroblasts differentiation, whereas blocking mechanotransduction by focal adhesion kinase inhibition disrupts this process, suggesting that matrix stiffness is a key driver of this lineage transition. Spatial mapping revealed colocalisation of the PI16+ and COMP+ subsets in extracellular matrix-dense regions, highlighting the functional relevance of this relationship in fibrotic progression. Conclusions: Our findings suggest that increased matrix stiffness promotes fibroblast precursor differentiation into SFRP2+ COMP+ PU.1+ myofibroblasts, thereby sustaining the vicious cycle of persistent fibrosis in absence of inflammatory triggers. These insights reveal new aspects of fibrosis pathogenesis and highlight biomechanical signals as therapeutic targets in SSc.
CRIS-Team Scopus Importer:2025-07-04

Microglial expression of CD83 governs cellular activation and restrains neuroinflammation in experimental autoimmune encephalomyelitis - Sinner, Pia; Peckert-Maier, Katrin; Mohammadian, Hashem; Kuhnt, Christine; Draßner, Christina; Panagiotakopoulou, Vasiliki; Rauber, Simon; Linnerbauer, Mathias; Haimon, Zhana; Royzman, Dmytro; Kronenberg-Versteeg, Deborah; Ramming, Andreas; et al. (Nature Communications, 2023)
Microglial activation during neuroinflammation is crucial for coordinating the immune response against neuronal tissue, and the initial response of microglia determines the severity of neuro-inflammatory diseases. The CD83 molecule has been recently shown to modulate the activation status of dendritic cells and macrophages. Although the expression of CD83 is associated with early microglia activation in various disease settings, its functional relevance for microglial biology has been elusive. Here, we describe a thorough assessment of CD83 regulation in microglia and show that CD83 expression in murine microglia is not only associated with cellular activation but also with pro-resolving functions. Using single-cell RNA-sequencing, we reveal that conditional deletion of CD83 results in an over-activated state during neuroinflammation in the experimental autoimmune encephalomyelitis model. Subsequently, CD83-deficient microglia recruit more pathogenic immune cells to the central nervous system, deteriorating resolving mechanisms and exacerbating the disease. Thus, CD83 in murine microglia orchestrates cellular activation and, consequently, also the resolution of neuroinflammation.
CRIS-Team Scopus Importer:2023-08-11

Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

Noncanonical WNT5A controls the activation of latent TGF-β to drive fibroblast activation and tissue fibrosis - Trinh-Minh, Thuong; Chen, Chih-Wei; Tran-Manh, Cuong; Li, Yi Nan; Zhu, Honglin; Zhou, Xiang; Chakraborty, Debomita; Zhang, Yun; Rauber, Simon; Dees, Clara; Lin, Neng-Yu; Kah, Delf-Thorge Eric; et al. (Journal of Clinical Investigation, 2024)
Transforming growth factor β (TGF-β) signaling is a core pathway of fibrosis, but the molecular regulation of the activation of latent TGF-β remains incompletely understood. Here, we demonstrate a crucial role of WNT5A/JNK/ROCK signaling that rapidly coordinates the activation of latent TGF-β in fibrotic diseases. WNT5A was identified as a predominant noncanonical WNT ligand in fibrotic diseases such as systemic sclerosis, sclerodermatous chronic graft-versus-host disease, and idiopathic pulmonary fibrosis, stimulating fibroblast-to-myofibroblast transition and tissue fibrosis by activation of latent TGF-β. The activation of latent TGF-β requires rapid JNK- and ROCK-dependent cytoskeletal rearrangements and integrin αV (ITGAV). Conditional ablation of WNT5A or its downstream targets prevented activation of latent TGF-β, rebalanced TGF-β signaling, and ameliorated experimental fibrosis. We thus uncovered what we believe to be a novel mechanism for the aberrant activation of latent TGF-β in fibrotic diseases and provided evidence for targeting WNT5A/JNK/ROCK signaling in fibrotic diseases as a new therapeutic approach.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Dermatology; Fibrosis; Pulmonology

POS0156 BONE DENSITY, MICROSTRUCTURE AND BIOMECHANICS OVER A 7-YEAR OBSERVATION PERIOD IN RHEUMATOID ARTHRITIS AND PSORIATIC ARTHRITIS - INFLUENCE OF AUTOIMMUNITY, DISEASE ACTIVITY AND BIOLOGICAL DMARD TREATMENT - Kemenes, Stephan; Tascilar, Koray; Kleyer, Arnd; Minopoulou, Ioanna; Fagni, Filippo; Zekovic, Ana; Isnardi, C. A.; Liphardt, Anna-Maria; Bayat, Sara; Schuster, Louis; Schett, Georg; Rauber, Simon (Annals of the Rheumatic Diseases, 2023)
Background Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA) are characterized by a deterioration of bone mass, bone microstructure and biomechanics [1, 2]. However, little evidence is available on the long-term evolution of these bone properties and the impact of autoimmunity, disease activity and targeted anti-inflammatory therapy. Objectives To evaluate the longitudinal course of peripheral volumetric bone mineral density (vBMD), microstructure and biomechanics in patients with seropositive RA (RA+), seronegative RA (RA-) and PsA (i) by diagnosis (ii) disease activity and (iii) ever use of biologic/targeted synthetic (b/ts) DMARDs. Methods RA+, RA-, PsA patients who had at least one high-resolution CT scan were included. Prospectively collected longitudinal data from the distal radius. vBMD, microstructure and biomechanical properties were assessed and data on treatments and disease activity (DAS-28) were collected. We described and summarized the time course of these measurements, using linear regression models as age and sex adjusted time-conditional means and mean differences by disease category, time-varying weighted average disease activity and intervening b/tsDMARD treatments. Results We analyzed 946 scans from 412 patients (193 RA+, 68 RA-, 151 PsA) with a median CT follow-up duration of 24 months (IQR 0 to 47). (Table 1). Overall, bone quality showed a downward course over time. RA+ patients showed lower total and trabecular bone densities compared to patients with psoriatic arthritis throughout the time course. (Figure 1a). RA+ patients also showed decreasing trabecular number with increasing trabecular thickness, trabecular irregularity and trabecular separation over time in comparison to PsA (Figure 1 b) suggesting a gradual disappearance of the thinner trabeculae. We detected significant time/DAS-28 interactions in PSA patients indicating faster cortical bone loss over time with increasing DAS-28 (p interaction =0.049), in RA- patients showing faster trabecular bone loss over time with higher disease activity (p.interaction 0.044) and in RA+ patients for trabecular density (p interaction 0.038), bone stiffness (p interaction 0.022) and failure load (p interaction 0.034) indicating a faster deterioration of bone quality over time with increasing disease activity. Interestingly, RA+ patients exposed to b/tsDMARDs had numerically lower bone density compared to unexposed patients, whereas the temporal pattern suggested a more stable vBMD over time as opposed to a deteriorating pattern in the unexposed. However, the uncertainty in these analyses was large and none of the time-exposure interactions or pairwise differences over time between ever vs. never exposed categories were significant. Conclusion Autoimmunity impairs bone health over time and is particularly associated with impaired trabecular bone quality. Good control of disease activity in RA+, RA-, and PsA patients may be helpful in preventing bone loss and deterioration of bone microstructure, and biomechanics. Specific contribution of b/tsDMARDs to the time course of bone quality at the radius needs further clarificatio
Keywords: Inflammatory arthritides; Disease-modifying Drugs (DMARDs); Imaging

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

PU.1 INHIBITOR DB1976 CONTROLS FIBROBLAST POLARIZATION IN SYSTEMIC SCLEROSISAND LEADS TO REGRESSION OF FIBROSIS IN DIFFERENT MODELS OF ORGAN FIBROSIS - Wohlfahrt, Thomas; Rauber, Simon; Luber, Markus; Soare, Alina; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Karouzakis, Emmanuel; Kiener, Hans; Pachera, Elena; Dees, Clara; Kreuter, Alexander; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid

Resolution of inflammation by interleukin-9-producing type 2 innate lymphoid cells - Rauber, Simon; Luber, Markus; Weber, Stefanie; Maul, Lisa; Soare, Alina; Wohlfahrt, Thomas; Lin, Neng-Yu; Dietel, Katharina; Bozec, Aline; Herrmann, Martin; Kaplan, Mark H.; Weigmann, Benno; et al. (Nature Medicine, 2017)
Inflammatory diseases such as arthritis are chronic conditions that fail to resolve spontaneously. While the cytokine and cellular pathways triggering arthritis are well defined, those responsible for the resolution of inflammation are incompletely characterized. Here we identified interleukin (IL)-9-producing type 2 innate lymphoid cells (ILC2s) as the mediators of a molecular and cellular pathway that orchestrates the resolution of chronic inflammation. In mice, the absence of IL-9 impaired ILC2 proliferation and activation of regulatory T (Treg) cells, and resulted in chronic arthritis with excessive cartilage destruction and bone loss. In contrast, treatment with IL-9 promoted ILC2-dependent Treg activation and effectively induced resolution of inflammation and protection of bone. Patients with rheumatoid arthritis in remission exhibited high numbers of IL-9(+) ILC2s in joints and the circulation. Hence, fostering IL-9-mediated ILC2 activation may offer a novel therapeutic approach inducing resolution of inflammation rather than suppression of inflammatory responses.
EVALuna2:13255

TEMPORAL MIGRATION OF IMMUNE CELLS FROM PSORIATIC SKIN TO JOINTS INITIATING SYNOVIAL INFLAMMATION IN PSORIATIC ARTHRITIS - Raimondo, Maria Gabriella; Rauber, Simon; Xu, Cong; Mohammadian, Hashem; Vogg, Mario; Anchang, Charles Gwellem; Rigau, Aleix; Luber, M.; Labinsky, Hannah; Soare, A.; Distler, Jörg; Fearon, U.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

TGF beta Promotes Fibrosis By MYST1-Dependent Epigenetic Regulation of Autophagy - Zehender, Ariella; Lin, Neng-Yu; Stefanica, Adrian; Chen, Chih-Wei; Soare, Alina; Wohlfahrt, Thomas; Rauber, Simon; Bergmann, Christina; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (2017)
EVALuna2:33446

TGFβ promotes fibrosis by MYST1-dependent epigenetic regulation of autophagy - Zehender, Ariella; Li, Yi-Nan; Lin, Neng Yu; Stefanica, Adrian; Nüchel, Julian; Chen, Chih-Wei; Hsu, Hsiao Han; Zhu, Honglin; Ding, Xiao; Huang, Jingang; Shen, Lichong; Györfi, Andrea-Hermina; et al. (Nature Communications, 2021)
Activation of fibroblasts is essential for physiological tissue repair. Uncontrolled activation of fibroblasts, however, may lead to tissue fibrosis with organ dysfunction. Although several pathways capable of promoting fibroblast activation and tissue repair have been identified, their interplay in the context of chronic fibrotic diseases remains incompletely understood. Here, we provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic effects. TGFβ induces autophagy in fibrotic diseases by SMAD3-dependent downregulation of the H4K16 histone acetyltransferase MYST1, which regulates the expression of core components of the autophagy machinery such as ATG7 and BECLIN1. Activation of autophagy in fibroblasts promotes collagen release and is both, sufficient and required, to induce tissue fibrosis. Forced expression of MYST1 abrogates the stimulatory effects of TGFβ on autophagy and re-establishes the epigenetic control of autophagy in fibrotic conditions. Interference with the aberrant activation of autophagy inhibits TGFβ-induced fibroblast activation and ameliorates experimental dermal and pulmonary fibrosis. These findings link uncontrolled TGFβ signaling to aberrant autophagy and deregulated epigenetics in fibrotic diseases and may contribute to the development of therapeutic interventions in fibrotic diseases.
CRIS-Team Scopus Importer:2021-08-06

The Potential of OMICs Technologies for the Treatment of Immune-Mediated Inflammatory Diseases - Anchang, Charles Gwellem; Xu, Cong; Raimondo, Maria Gabriella; Atreya, Raja; Maier, Andreas; Schett, Georg; Zaburdaev, Vasily; Rauber, Simon; Ramming, Andreas (International Journal of Molecular Sciences, 2021)
Immune‐mediated inflammatory diseases (IMIDs), such as inflammatory bowel diseases and inflammatory arthritis (e.g., rheumatoid arthritis, psoriatic arthritis), are marked by increasing worldwide incidence rates. Apart from irreversible damage of the affected tissue, the systemic nature of these diseases heightens the incidence of cardiovascular insults and colitis‐associated neo-plasia. Only 40–60% of patients respond to currently used standard‐of‐care immunotherapies. In addition to this limited long‐term effectiveness, all current therapies have to be given on a lifelong basis as they are unable to specifically reprogram the inflammatory process and thus achieve a true cure of the disease. On the other hand, the development of various OMICs technologies is consid-ered as “the great hope” for improving the treatment of IMIDs. This review sheds light on the pro-gressive development and the numerous approaches from basic science that gradually lead to the transfer from “bench to bedside” and the implementation into general patient care procedures.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Advanced imaging technologies; Immune‐mediated inflammatory diseases (IMIDs); Single‐cell RNA sequencing; Spatial sequencing

Type 2 Innate Lymphoid Cells - Cellular Source of Profibrotic Mediators Rapidly and Persistently Recruited in Experimental Fibrosis and Systemic Sclerosis - Weber, Stefanie; Wohlfahrt, Thomas; Rauber, Simon; Luber, Markus; Englbrecht, Matthias; Dees, Clara; Beyer, Christian; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (2016)
EVALuna2:35067

Type 3 Innate Lymphoid Cells in models of psoriasis and psoriatic arthritis - Raimondo, M. G.; Rauber, Simon; Distler, Jörg; Schett, Georg; Ramming, A. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic